A mild case of Cockayne syndrome with a novel start-loss variant of ERCC8 - Taro Matsuoka; Takeshi Yoshida; Kengo Kora; Naoko Yano; Yoshihiro Taura; Takashi Nakamura; Takenori Tozawa; Jun Mori; Tomohiro Chiyonobu (Human Genome Variation)
Abstract Cockayne syndrome (CS) is a progressive multisystem disorder characterized by growth failure, microcephaly, developmental delay, and photosensitivity. The characteristic symptoms appear during early childhood in most patients with CS. Herein, we report a mild case of CS with a novel start-loss variant in ERCC8 that did not show the characteristic symptoms of CS during early childhood and exhibited sudden growth failure after the age of 10 years.